Study of awareness, enrolment, and utilization of Ayushman Bharat Pradhan Mantri Jan Arogya Yojana in Gujarat, India - Thomas, Bigi; Raykundaliya, Dharmesh P.; Bhatt, Sonal; Vadhel, Ketal (International Journal Of Community Medicine And Public Health, 2023)
Background: Ayushman Bharat-Pradhanmantri Jan Arogya Yojana (AB-PMJAY) envisages complete financial protection for around 50 crores of identified poor and vulnerable Indian beneficiaries against their catastrophic health care needs. Awareness is a pre-requisite that ensures enrolment and utilization of any health insurance program. Being a newly implemented scheme, very few studies are reported on the level of awareness, enrolment, and utilization of the AB-PMJAY scheme as well as the sources of information and support to the beneficiaries from Gujarat. So, this study aims to assess the current status of awareness, enrolment, and utilization of AB-PMJAY in Gujarat. Methods: A multi-stage sampling method was used in this cross-sectional study in both rural and urban areas and altogether 1152 households were randomly selected from three districts of Gujarat. Ten trained field investigators collected data with the help of a structured interview schedule. Results: AB-PMJAY is popular in Gujarat, with 24% high-level awareness and 47.8% moderate-level awareness. Out of 1152 households, 82.9% had AB-PMJAY cards, with a 43.3% utilization rate. Factors affecting awareness include area of living, religion, and caste. While 22.9% reported out-of-pocket (OOP) expenditure with AB-PMJAY benefits, 15.1% reported non-utilization of their AB-PMJAY cards, despite needed. ASHA workers and Ayushman Mitras were the major sources of information. Conclusions: The reported utilization rate in this study was only 43.3%, despite having impressive awareness and enrolment rates. The OOP costs must be reduced, and the issues that prevented households from using the AB-PMJAY benefits despite their need must be addressed.